Manual neuronavigation for superior semicircular canal dehiscence surgery - Altamami, Nasser; Khoury, Michel; Saliba, Issam (Frontiers in Neurology, 2023)
Background: intraoperative identification of the superior semicircular canal (SSCC) dehiscence through Middle Cranial Fossa Approach (MCFA) remains a difficult endeavor without a neuronavigation system. Given these challenges, we sought to propose a technique to localize the SSCC dehiscence intraoperatively using certain anatomical landmarks. Method: Three anatomical landmarks should be identified on preoperative radiological images; the distance from the squamous part of the temporal bone to the dehiscent SSCC, the lower limit of the craniotomy and the exact location of the craniotomy in relation to the bony external auditory canal. The use of these landmarks intraoperatively can allow the surgeon to correctly identify the position of the SSCC. Two instructional videos explaining this technique were devised. Conclusion: The proposed Manual Neuronavigation technique seems to be accurate, safe, and cost-effective alternative technique used in SSCC dehiscence surgery.